The Concept and Scope of Accounting Policy in Polish and International Accounting Regulations - Stępień, Konrad (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2019)
Accounting policy can be interpreted and defined in numerous ways. It is often associated with the principles of accounting. The scope of accounting policy is also determined in a variety of ways.The study examines accounting policy in the context of accounting principles and defines the concept of accounting policy. It compares the scope of accounting policy defined in Polish and international accounting regulations and indicates differences in this area. In so doing, it analyses the subject literature and legal acts, comparing them and drawing deductions.Currently, Polish legal regulations do not match international regulations in terms of how they define accounting policy and its scope. While Poland is gradually adjusting its regulations to EU regulations, the scope of accounting policy has still not been standardized.The analysis shows that accounting policy is not determined by accounting principles, but by the choosing if these principles. The selected accounting policies are the result of accounting policy and evidence of its implementation. On the other hand, in accounting regulations (Polish Accounting Act, IAS), accounting policy is synonymous with the principles or as detailed accounting solutions, which is incorrect. In addition, there is considerable discrepancy in the scope of accounting policy in the Polish Accounting Act and IAS.